Federalism and decentralization in health care : a decision space approach - Bossert, Thomas J.; Marchildon, Gregory P., 1956- (University of Toronto Press, 2018)
"A unique scholarly contribution to the field of comparative federalism, decentralization, and health care policy. This collection offers a systematic perspective on health care decentralization in a diverse group of federal countries that includes high-income (Switzerland, Canada, & Germany), high middle-income (Brazil, Mexico and South Africa) and low middle income (Nigeria & Pakistan) countries. This collecton should be a valuable resource for those studying health care policy in federal systems and especially those interested in comparative aspects of the topic."--